Advancements in Titanium Dioxide Nanotube-Based Sensors for Medical Diagnostics: A Two-Decade Review - Joydip Sengupta; Chaudhery Mustansar Hussain (Nanomaterials)
Over the past two decades, titanium dioxide nanotubes (TiO2 NTs) have gained considerable attention as multifunctional materials in sensing technologies. Their large surface area, adjustable morphology, chemical stability, and photoactivity have positioned them as promising candidates for diverse sensor applications. This review presents a broad overview of the development of TiO2 NTs in sensing technologies for medical diagnostics over the last two decades. It further explores strategies for enhancing their sensing capabilities through structural modifications and hybridization with nanomaterials. Despite notable advancements, challenges such as device scalability, long-term operational stability, and fabrication reproducibility remain. This review outlines the evolution of TiO2 NT-based sensors for medical diagnostics, highlighting both foundational progress and emerging trends, while providing insights into future directions for their practical implementation across scientific and industrial domains.